Preparation of biodegradable polypropylene carbonate-polylactic acid core yarn by electrospinning and its antibacterial finishing - Zhou, Ning; Zhu, Ling; Dong, Yi-Hang; Kim, Ick Soo; Gao, Hong-Guo; Zhang, Ke-Qin (Frontiers in Materials, 2023)
With the improvement of living standards, people’s awareness of health and environmental protection continues to strengthen. The production of textiles with antibacterial functions is one of the effective ways to protect people from or reduce bacterial invasion. Therefore, textiles with antibacterial functions are increasingly favored by people. At the same time, due to the impact of global warming, people are committed to reducing carbon emissions in all aspects of life. The biodegradable material polypropylidene carbonate (PPC) that can consume carbon dioxide (CO2) in the production process fully conforms to people’s environmental protection concept. However, polypropylidene carbonate itself has poor thermal stability and narrow application range. Polypropylidene carbonate thermoplastic polyurethane (PPC-TPU) is obtained by chain extension modification, which can broaden the application range of polypropylidene carbonate. To develop a yarn with excellent antibacterial and mechanical properties, which can be woven into fabrics for medical applications while taking into account environmental protection and degradability, the antibacterial yarn in this article was prepared by electrospinning using PPC-TPU and polylactic acid (PLA) yarn as raw materials. The preparation process was optimized by adjusting the supply speed, winding collection speed and horn barrel speed, and the optimal concentration of antimicrobial agent was explored by adding different concentrations of benzalkonium bromide antimicrobial. Through the characterization of the properties of the materials, we believe that PPC-PLA yarn with the addition of 5% benzalkonium bromide has broad development prospects in the medical field due to its excellent mechanical and antibacterial properties.